Introducing Internationalisation at Home: Learning satisfaction under the Content and Language Integrated Learning approach. Issue 1 (1st March 2022) - Gosling, Mark; Yang, Wenhsien
Abstract: Taiwan higher education institutions are employing two strategies: Internationalisation at Home (IaH) to promote domestic students' international exposure and awareness, and Content and Language Integrated Learning (CLIL) to promote language skills and professional knowledge. Higher education institutions recognise the synergy of these two strategies and the opportunity through them to attract international students to study in an English-speaking classroom. What is not known is the reaction of the domestic CLIL students in English as a Foreign Language settings to the introduction of native English speakers into their classroom, and this is the focus of this exploratory study. Results suggest that the domestic students are largely positive about the engagement of the exchange students but also raise the issues of internationalised curriculum and intercultural mixing in the monolingual context.